MENCARI PENYEBAB KECELAKAAN DI JALAN TOL SURABAYA-GEMPOL DENGAN ANALISA FREKUENSI DAN CROSSTABULATION - Harry Patmadjaja (Institute of Research and Community Outreach - Petra Christian University, 1999)
Three hunderd and thirteen data of accident between January 1997 and December 1997 were used to determine causes of accident in Surabaya-Gempol Surabaya-Gempol Tol Road. The evaluations were done using Frequency, and Crosstabulation analysis. Frequency analysis was used to determine the blackspots, whereas Crosstabulation analysis using Pearson chi-square and the contingency coefficient was used to identify corelations between fatality of accident, major cause of accident, variables causing major accident and other variables causing accident.The analysis concluded that fatal accidents were caused by sleepiness. The variables causing the accident were; the driver’s physical condition, close spacing of the vehicles and tyre failures. Fatal, and nonfatal accidents were caused by variables as type of vehicle, vehicle manuever and the age of driver as well as the vehicle.